PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA DI SD NEGERI 25 PALEMBANG - Dessy Cahya Utamy; Muhammad Juliansyah Putra; Farhan yadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whwther there is an influence of giving Rewards on student’s learning motivation at SD Negeri 25 Palembang. The research also aims to identify the obstacles and challenges that may arise during the implementation of Rewards in enhancing student’s learning motivastion. This research uses a quantitative method with a correlation type. The population in this study consists of all students at SD Negeri 25 Palembang, totaling 591 students. The sampling technique used is non-prbability sampling with a purposive sampling method, involving 30 students from class IIIA. Data collection techniques in this study include questionnaires, interviews, and documentation. Based on the kolmogrov-smirnov normality last, the significance value for Rewards ins 0,335 > 0,05 and for learning motivation is 0,605 > 0,05, indication that the data are normally distributed. The result og the linearity test shows a significance value for deviation from linarity 0f 0,857 > 0,05, which means the data are linear. The hypothesis test using pearson product moment correlation shows a significance value of 0,438 < 0,05. This means the Ha is accepted and Ho is rejected. Therefore, it can be concludes that there is a significant influence of giving Reward on student’s learning motivation at SD Negeri 25 Palembang